(untitled) (MAUSAM, 1974)
With the help of the observed radiosonde and convective rainfall data for two Indian stations, three methods of computing convective rainfall in numerical models were compared. It was found that the rainfall computed by all the methods is comparable to the observed rainfall. However computed rainfall differs considerably from one method to the other.